2017
DOI: 10.1186/s12909-017-0927-y
|View full text |Cite
|
Sign up to set email alerts
|

Is the delivery of a quality improvement education programme in obstetrics and gynaecology for final year medical students feasible and still effective in a shortened time frame?

Abstract: BackgroundTeaching clinical audit skills to nascent health professionals is one strategy to improve frontline care. The undergraduate medical curriculum at the University of Auckland provides improvement science theory and skills in Year 5 teaching, and the opportunity to put this into practice during an Obstetrics and Gynaecology (O&G) clinical attachment in Year 6. In 2015, a revised medical school curriculum at the university resulted in a planned reduction of the O&G attachment from five weeks to four, nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Likewise, Kool and colleagues 7 used the CIPP (Context, Input, Process and Product) evaluation model to assess whether the revised medical school program (5 weeks shortened to 4 weeks) would support completion of a quality improvement (QI) project for sixth year medical students without negatively impacting clinical trainers or clinical services. Student perceptions on QI projects improved in 7 out of 9 domains when compared to before and after program revisions.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Kool and colleagues 7 used the CIPP (Context, Input, Process and Product) evaluation model to assess whether the revised medical school program (5 weeks shortened to 4 weeks) would support completion of a quality improvement (QI) project for sixth year medical students without negatively impacting clinical trainers or clinical services. Student perceptions on QI projects improved in 7 out of 9 domains when compared to before and after program revisions.…”
Section: Discussionmentioning
confidence: 99%
“…This was at odds with some students describing the need for time to orientate themselves to the ward before they felt comfortable enough with the systems and processes to be able to identify an appropriate quality improvement project (James et al, 2016). Students' experiences were that the amount of time allocated to complete the quality improvement project; either 4 weeks (Kool et al, 2017) or 10 weeks (Kyrkjebø, 2006) TA B L E 2 (Continued)…”
Section: Quality Improvement Partnership Themesmentioning
confidence: 99%
“…In some studies, the student quality improvement projects were reported to have been implemented into healthcare organisation practice (Christiansen et al, 2010;Gleason et al, 2019;James et al, 2016); however, no detail of the longer-term evaluation or impacts were described. For example, Gjessing et al (2014) stated that quality improvement projects may be integrated by healthcare staff into their daily patient care and Kool et al (2017) described quality improvement project implementation on a continuum, with some not being implemented at all to others being 'fully integrated' (p. 6).…”
Section: Impacts Of Quality Improvement Partnershipsmentioning
confidence: 99%
“…68 All parts of the CIPP evaluation model are completed throughout the duration of the programme, including interim product evaluation to address any issues resulting in important outcomes not being achieved. 68 Example: Kool et al 69 describe data collection, analysis and results for each of the context, input, process and product evaluations of a quality improvement education programme in final year medical students.…”
Section: Context Input Process and Product (Cipp) Evaluationmentioning
confidence: 99%
“…Example: Kool et al 69 describe data collection, analysis and results for each of the context, input, process and product evaluations of a quality improvement education programme in final year medical students.…”
Section: Outcome Evaluation Is Not Enough—how To Move Beyond Outcome ...mentioning
confidence: 99%